PENERAPAN BLENDED LEARNING BERBASIS EDMODO TERHADAP MINAT DAN HASIL BELAJAR SISWA SMAN 9 PONTIANAK - Angraini, Mega Restu; Muharini, Rini; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study were to describe the learning interest and learning outcome of class XII students SMAN 9 Pontianak using edmodo-based blended learning model on solubility and solubility product topic after being given remedial and enrichment using edmodo. Research design was was experimental study with one-shot case study. Students of class XII MIA 1 were selected as sample using cluster random sampling technique. Collecting data technique were measurement, indirect communication, direct communication and observation. Learning outcome test, interest questionnaire, observation sheet and interview guidelines were used to collect data. The results revealed that the students were interested in learning using an edmodo-based blended learning model with interprestation of interest in learning was very strong categorie (85,8 %). The average results of learning outcomes of the remedial and enrichment using edmodo test was very good categorie (80,5).Keywords: Edmodo-based Blended Learning Model, Interest, learning outcomes, solubility and solubility productÂ Â